Microbial and abiotic nitrous oxide cycling in the water column of meromictic, iron-rich Lake La Cruz, Spain, 2015-2017 - Tischer, Jana; Zopfi, Jakob; Frey, Claudia; Brand, Andreas; Oswald, Kirsten; Jegge, Corinne; Frame, Caitlin H; Miracle, María R; Sòria-Perpinyà, Xavier; Vicente, Eduardo; Lehmann, Moritz F (PANGAEA, 2022)
We investigated the microbial and abiotic N2O cycle in the water column of iron-rich, meromictic Lake La Cruz, Spain, during two sampling campaigns in March 2015 and March 2017. At the deepest point of the lake, we used a profiling in situ analyzer equipped with several probes and optodes to detect physicochemical parameters. In addition, we collected water column samples via an in situ pump in order to analyze concentrations of N, S, and Fe species as well as isotope characteristics of several N species. In 2017, we used a Niskin bottle to take water samples from 8.0 and 14.5 m depth for two types of incubation experiments. In the first set of experiments, we added 15N-labeled substrates, and in some incubations Fe2+, to filtered and unfiltered lake water, and analyzed the produced N2O, N2, and NH4+. In the other experiment, we determined the N and O isotope effects of NO2- and N2O during chemodenitrification (reaction of NO2- and Fe2+) in anoxic and sterile lake water from 14.5 m depth.
Keywords: 15N-tracer; anoxia; chemodenitrification; Denitrification; ferruginous; meromixis; N2O production rates; N2O site preference; nitrification; nitrifier denitrification; nitrogen isotopes; nitrous oxide; oxycline; water column